A protective measles virus-derived vaccine inducing long-lasting immune responses against influenza A virus H7N9 - Cindy Hörner; Anna H. Fiedler; Bianca S. Bodmer; Lisa Walz; Vivian A. Scheuplein; Stefan Hutzler; Mikhail N. Matrosovich; Veronika von Messling; Michael D. Mühlebach (npj Vaccines, 2023)
Abstract A novel Influenza A virus (subtype H7N9) emerged in spring 2013 and caused considerable mortality in zoonotically infected patients. To be prepared for potential pandemics, broadly effective and safe vaccines are crucial. Recombinant measles virus (MeV) encoding antigens of foreign pathogens constitutes a promising vector platform to generate novel vaccines. To characterize the efficacy of H7N9 antigens in a prototypic vaccine platform technology, we generated MeVs encoding either neuraminidase (N9) or hemagglutinin (H7). Moraten vaccine strain-derived vaccine candidates were rescued; they replicated with efficiency comparable to that of the measles vaccine, robustly expressed H7 and N9, and were genetically stable over 10 passages. Immunization of MeV-susceptible mice triggered the production of antibodies against H7 and N9, including hemagglutination-inhibiting and neutralizing antibodies induced by MVvac2-H7(P) and neuraminidase-inhibiting antibodies by MVvac2-N9(P). Vaccinated mice also developed long-lasting H7- and N9-specific T cells. Both MVvac2-H7(P) and MVvac2-N9(P)-vaccinated mice were protected from lethal H7N9 challenge.